Hubungan Pola Makan, Aktivitas Fisik, dan Tingkat Stres dengan Kadar Glukosa Darah pada Pasien Diabetes di Komunitas Perkotaan Makassar - Masahuddin La; Edy Supardi; Iis Ismayanti; Ayu Paneo (Wal'afiat Hospital Journal, 2026)
Introduction: Diabetes mellitus remains a global health problem, including in urban communities, and is influenced by lifestyle factors, particularly family dietary patterns, physical activity, and stress, which play a crucial role in glycemic control. This study aimed to analyze the relationship between family dietary patterns, physical activity, and stress with blood glucose control among patients with diabetes in urban communities of Makassar. Method: A total of 73 respondents were recruited, and data were collected using questionnaires. Results showed that dietary patterns (p = 0.000), adequate physical activity (p = 0.027), and stress levels (p = 0.000) were significantly associated with blood glucose control (p < 0.05) among patients with diabetes in urban Makassar. Discussion: Family support through the provision of healthy meals, home-cooked food habits, and regular physical activity played a protective role in glycemic control, whereas high psychological stress increased the risk of poor glycemic control. Therefore, diabetes management in urban communities should be conducted comprehensively by emphasizing family-based nutritional interventions, increased physical activity, and stress management as key components of blood glucose control. Conclusion: Healthy family dietary patterns, adequate physical activity, and lower stress levels are significantly associated with better glycemic control among patients with diabetes in urban communities of Makassar.